2016
DOI: 10.1038/am.2016.163
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanorings synthesized via a stress-driven collapse and etching mechanism

Abstract: Toroidal Au or Ag nanostructures are of particular interest due to their unique optical responses and superior catalytic applications. However, the fabrication of ring-like Au or Ag nanostructures is limited to either electron beam lithography or template techniques, thus hampering their applications. Here, we present a new stress-driven structure collapse and etching mechanism to synthesize Au nanorings via a direct one-pot solution-based chemical reaction. The nanoparticle-mediated recrystallization process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
(45 reference statements)
3
8
0
Order By: Relevance
“…For example, a similar growth mode has been observed in the growth of nonsymmetric ZnO nanodisks and nanorings, in which bis(2‐ethylhexyl) sulfosuccinate (NaAOT) serves as soft template for the limited growth of 2D nanostrcures . Similarly, in our recent study, in the case of Au nanoplate, hexagonal Au disks with one side smooth and the other concave was formed using PEG‐water soft template …”
supporting
confidence: 69%
See 2 more Smart Citations
“…For example, a similar growth mode has been observed in the growth of nonsymmetric ZnO nanodisks and nanorings, in which bis(2‐ethylhexyl) sulfosuccinate (NaAOT) serves as soft template for the limited growth of 2D nanostrcures . Similarly, in our recent study, in the case of Au nanoplate, hexagonal Au disks with one side smooth and the other concave was formed using PEG‐water soft template …”
supporting
confidence: 69%
“…When enough of KI and EG molecules connect together, 2D EG–KI soft templates will be formed in the synthesis solution, as shown in Figure C. This situation is similar to the 2D water‐PEG soft template in our recent work in which Au nanoplates have been synthesized …”
supporting
confidence: 64%
See 1 more Smart Citation
“…It has been previously reported that high-density crystallographic defects in the center of large semiconductor and metal nanoplates can lead to structural collapse and etching, forming ring- or frame-like structures. [3840] In contrast, the nanoplates (with a central pore) obtained here exhibit nearly perfect crystal lattices (Figure 1c). This is further demonstrated by the selected area electron diffraction (SAED) measurement taken from single Au nanoplate (Figure 1d) where the diffraction pattern can be attributed to single crystalline Au with parallel stacking faults.…”
mentioning
confidence: 84%
“…This line structure is different from other continuous and randomly oriented darker lines (pointed by the red arrows), which are commonly observed in thin Au nanoplates and have been attributed to bending. [37, 38] By analyzing the central region via HRTEM (Figure 1c and Figure S2), the average diameter of the pores is only 0.85 ± 0.08 nm. The yield of the Au nanoplates with nanopores are generally greater than 90%, in which ~ 60% of the nanoplates contain a single pore, whereas the others have two or three pores.…”
mentioning
confidence: 99%